ดัชนีชี้วัดผลการปฏิบัติงาน สำหรับระบบประกันคุณภาพ ISO 9001:2008 ของบริษัทรับเหมาก่อสร้างด้าน ก๊าซและน้ำมัน - สวรรค์ ฉัมมาลี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The purposes of this study were to make ISO 9001:2008 system, estimate the cost of the construction project quality management system, and evaluate the benefits in term of value after the administrators specified the target of KPI (Key Performance Indicators) in ISO 9001:2008 quality management system that Tesco Engineering Company, Kamphaeng Phet, was used in this this study. Tesco Engineering Company would prepare the system of ISO 9001:2008 quality management. The instruments in this study were questionnaires for asking about assets of making this system, and some experts from TÜV NORD Thailand to certify and monitor for a suitability and possibility of specifying the target. The first study was founded that the organized indicators were unable to be used 30%, so they should be improved. For the benefits, if they could be done, KPI would be valuable at 2,870,064 baht/year. The B/C ratio was 1.75 which was worth to invest on making system. Nevertheless, this study did not include any advantages for an auction in the future due to the certificate, and making KPI’s benefits were unreal the most. It was just an analysis and based on whether it could be done as such KPI.